2020
DOI: 10.5812/aapm.99764
|View full text |Cite
|
Sign up to set email alerts
|

Short-Term Efficacy of Epidural Injection of Triamcinolone Through Translaminar Approach for the Treatment of Lumbar Canal Stenosis

Abstract: Background: Epidural steroid injection is a non-operative minimally invasive procedure for pain relief in spinal canal stenosis. However, there is no significant consensus regarding its efficacy. Objectives: In this study, we aimed to evaluate the effectiveness of translaminar injection of triamcinolone in lumbar canal stenosis. Methods: In a retrospective study, we included 111 patients with MRI-confirmed spinal canal stenosis who were irresponsive to 12 weeks of conservative treatment and underwent epidural … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 25 publications
(26 reference statements)
1
3
0
Order By: Relevance
“…Only 18% of cases with severe LSCS demonstrated effective response to interlaminar ESI, whereas 30% of cases with moderate LSCS demonstrated effective pain alleviation. In addition, similar results were reported by Sabbaghan et al, 2020 [23] who demonstrated that the epidural steroid administration was significantly able to reduce the severity of LSCS pain through evaluation of VAS score which demonstrated that the mean pre-treatment VAS for lower limb pain was 7.4±1.5, which improved to 4.2±1.6 after the intervention (p< 0.001). Our results are supported by Kim et al, 2012 (24) who enrolled 20 cases with chronic low back pain to evaluate the efficacy of steroid administration in cases with chronic low back pain.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Only 18% of cases with severe LSCS demonstrated effective response to interlaminar ESI, whereas 30% of cases with moderate LSCS demonstrated effective pain alleviation. In addition, similar results were reported by Sabbaghan et al, 2020 [23] who demonstrated that the epidural steroid administration was significantly able to reduce the severity of LSCS pain through evaluation of VAS score which demonstrated that the mean pre-treatment VAS for lower limb pain was 7.4±1.5, which improved to 4.2±1.6 after the intervention (p< 0.001). Our results are supported by Kim et al, 2012 (24) who enrolled 20 cases with chronic low back pain to evaluate the efficacy of steroid administration in cases with chronic low back pain.…”
Section: Discussionsupporting
confidence: 85%
“…They found that cases suffered from low back pain for about 12 month with 5.6±1.0 average pre-treatment VAS score. Further, Sabbaghan et al, 2020 [23] recruited a retrospective research including 111 cases with MRI-confirmed spinal canal stenosis (SCS) who underwent epidural administration to evaluate the effectiveness of translaminar administration of triamcinolone in LSCS. The results demonstrated that the mean pre-treatment VAS for lower limb pain was 7.4±1.5.…”
Section: Discussionmentioning
confidence: 99%
“…The administration of steroids via epidural injection as a nonsurgical treatment for lumbar spinal stenosis (LSS) has been analyzed in various studies but, again, there is not a clear consensus regarding their efficacy in relieving the symptoms, especially in the long-term follow-ups. It is important to notice that a consistent number of studies have reported some degree of benefit, especially regarding short-term improvements [ 53 , 54 , 55 , 56 , 57 , 58 , 59 ] ( Table 2 ). A more favorable response seems to be associated with relative youth, female sex and patients with single level stenosis, while BMI, MRI severity and the dimension of the spinal canal are probably not predictive [ 55 , 60 , 61 ].…”
Section: Resultsmentioning
confidence: 99%
“…However, because of the transient pharmacological effect, the injection route of corticosteroids was changed into epidural space. Several studies have supported the efficacy of ESI in spinal disease [ 2 4 ]. Transforaminal epidural steroid injection (TFESI) is used to relieve pain and reduce the potential need for surgery [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%